THE LEVEL OF SATISFACTION OF ANTENATAL CARE (ANC) PATIENTS WITH THE QUALITY OF HEALTH SERVICES AT THE KUTA BARO HEALTH CENTER DISTRICT ACEH BESAR - Muliana Muliana; Ummu Aiman (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Patient satisfaction is one of the main indicators of the standard of a health facility as a result of health services. The satisfaction of patients can be achieved by developing a service system that is responsive to patient complaints, which in turn will minimizes costs and time and maximizes the impact of services on patients. It is of great importance to consider patient satisfaction in the context of health services, as this can provide insight into the quality of the service provided. Consequently, the objective of this study was to ascertain the level of satisfaction of patients receiving antenatal care (ANC) at the Kuta Baro Health Center in Aceh Aceh Regency the year is 2024. This study employs an analytic approach with a cross-sectional research design. The population under investigation consisted of all pregnant women who visited the Kuta Baro Health Center between September and October 2024. A total sampling technique was utilized, and a chi-square statistical test was conducted to analyze the data. Univariate and bivariate data analysis techniques were employed to examine the findings. The findings of the study, as reported by respondents who had sought examination at the health center, indicated a lack of satisfaction with the quality of services provided by health workers. This study demonstrates a correlation between the level of satisfaction of antenatal care (ANC) patients with the quality of health services at the Kuta Baro Health Center in Aceh Besar Regency in 2024, with a P-value of 0.003, which is less than 0.05. It is recommended that pregnant women adhere to the recommended schedule for antenatal care (ANC) examinations. It is hoped that the findings of this study will enhance the knowledge of pregnant women regarding the quality of services provided by health workers, particularly in relation to.